2020
DOI: 10.1186/s12940-020-00647-1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Perflouroalkyl acids and foetal and maternal thyroid status: a review

Abstract: Background Exposure to perfluorinated-alkyl-acids (PFAAs) is ubiquitous. PFAAs are hormone-disrupting compounds that are strongly suspected to affect mother-child-health such as fetal growth. Thyroid disruption is a plausible mechanism of action. We aim to summarize the epidemiological evidence for the relation between prenatal and postnatal exposure to PFAAs and disruption of thyroid homeostasis in mothers and/or infants. Method Fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 87 publications
(360 reference statements)
1
14
1
Order By: Relevance
“…the estrogen and androgen receptors and thus modulating their signaling 2 , 3 . In addition, studies show that POPs can disrupt thyroid hormones in rodent’s such as mice and rats 1 , 4 6 as well as in human 7 , 8 . Heavy metals are considered systemic toxicants known to affect and damage multiple organ systems even at lower levels of exposure and some of them are classified as ‘known’ and ‘probable’ human carcinogens 9 .…”
Section: Introductionmentioning
confidence: 99%
“…the estrogen and androgen receptors and thus modulating their signaling 2 , 3 . In addition, studies show that POPs can disrupt thyroid hormones in rodent’s such as mice and rats 1 , 4 6 as well as in human 7 , 8 . Heavy metals are considered systemic toxicants known to affect and damage multiple organ systems even at lower levels of exposure and some of them are classified as ‘known’ and ‘probable’ human carcinogens 9 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, several epidemiological studies have identified associations between PFHxS and altered liver, thyroid, energy and lipid metabolism, protein biosynthesis, and immune function, which may be indirectly involved in the reproductive toxicity caused by PFHxS [55][56][57][58]. In addition, AVPV-and ARC-kisspeptin neurons express prolactin receptors, suggesting the possible participation of prolactin in the toxicity of PFHxS [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several epidemiological studies have identi ed associations between PFHxS and altered liver, thyroid, energy and lipid metabolism, protein biosynthesis, and immune function, which may be indirectly involved with the reproductive toxicity caused by PFHxS [46][47][48][49]. In addition, AVPV-and ARC-kisspeptin neurons express prolactin receptors, suggesting the possible participation of prolactin in the toxicity of PFHxS [50][51].…”
Section: Discussionmentioning
confidence: 99%